Transition 114 : Transition: the Magazine of Africa and the Diaspora (Book collections on Project MUSE., 2014)
Published three times per year by Indiana University Press for the Hutchins Center at Harvard University, Transition is a unique forum for the freshest, most compelling ideas from and about the black world. Since its founding in Uganda in 1961, the magazine has kept apace of the rapid transformation of the African Diaspora and has remained a leading forum of intellectual debate. This issue of Transition-""Gay Nigeria""-pays tribute to those who ""agitate the establishment."" Gay Nigeria grapples with anti-gay sentiment in Africa through the case-in-point of Nigeria's recent Same-Sex Marriage P.